Fertility anxiety vs. anti-fertility anxiety: exploring Chinese women’s conflicting attitudes toward childbearing through social media - Li, Weiwei; Zhou, Yuchan (Frontiers in Psychology, 2025)
IntroductionAmid a global decline in fertility rates, China’s consistently low birth rate has highlighted the importance of understanding the fertility attitudes of women of childbearing age. While previous studies have largely focused on fertility anxiety, less attention has been paid to anti-fertility anxiety—women’s psychological resistance to societal pressures and expectations surrounding childbearing. To address this research gap, this study explores how women construct and articulate these seemingly conflicting attitudes, as well as the sociopsychological mechanisms that enable their coexistence.MethodsUsing grounded theory and natural language processing techniques, the study analyzed 4,495 Weibo posts (fertility anxiety = 2,761; anti-fertility anxiety = 1,734) through three-level coding, semantic network analysis, and sentiment analysis.ResultsThe findings indicate that both fertility anxiety and anti-fertility anxiety are shaped by sociocultural and media narratives at the macro level, family and workplace dynamics at the meso level, and personal values and experiences at the micro level. Fertility anxiety discourse is primarily situated at the macro and meso levels, reflecting women’s feelings of insecurity and powerlessness in the face of societal pressures, maternal penalties and unequal family burdens. Anti-fertility anxiety is more rooted in micro-level expression, emphasizing reproductive autonomy and identification with motherhood amid a broader feminist awakening. The emotional tendency of fertility anxiety is predominantly negative, with intensity decreasing from the macro to the meso and micro levels. Anti-fertility anxiety is associated with more positive emotions, with emotional intensity declining from the micro to the meso and macro levels.ConclusionThis study highlights the psychological tension between structural constraints and subjective desires in women’s fertility decisions, reinforcing explanations for conflicting fertility attitudes in the context of social media empowerment. These insights contribute to the conceptual understanding of anti-fertility anxiety and also offer practical recommendations for enhancing women’s reproductive autonomy, psychological well-being, and fertility-related policies and support systems.